Legal language and power: a critical discourse analysis of anti-corruption laws in Indonesia - Dani Setiaji (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: Corruption in Indonesia remains a persistent challenge, and the Anti-Corruption Law (UU Tipikor) has long been criticized for embedding state-centered framings and ambiguous provisions that complicate consistent enforcement. Objective: The purpose of this study is to critically examine how the language of anti-corruption law constructs ideological authority and distributes institutional power. Method: Using a qualitative design, this research integrates Critical Discourse Analysis, legal semiotics, and modality pragmatics to analyze statutes, regulations, judicial decisions, and institutional documents as a comprehensive corpus. Results: The findings reveal three central patterns: first, ideological framings foreground kerugian negara (state losses) and kepentingan umum (public interest) while marginalizing direct reference to citizens; second, key terms such as penyelenggara negara, gratifikasi, and patut diduga demonstrate symbolic ambiguity that sustains state authority yet undermines legal certainty; third, the predominance of discretionary modality (dapat) over obligatory terms (wajib, harus) illustrates how linguistic structures empower enforcement bodies while weakening mandatory accountability. Implication: The implication is that reform efforts must address not only institutional design but also the ideological framing and linguistic construction embedded within legal texts. Novelty: This study interrogates how the linguistic and semiotic construction of anti-corruption law in Indonesia sustains institutional authority while embedding ambiguity that shapes power distribution and enforcement practices.